Lealtad en el exilio: afiliaciones concéntricas y enunciación hispanista en la Historia antigua de México (1780) de Francisco Javier Clavijero (1731-1787) - Silva Guerrero, Fernando J. (2016)
This article presents an analysis of the identity links as enunciated in the Historia antigua de México (1780), written by the Novohispano Jesuit Francisco Javier Clavijero (1731-1787). Facing the degrading European theses which, during the mid-18th century, had tried to justify the inferiority of the population of the Americas, Clavijero built his defense for the people of the valley of Anahuac not only from a strictly criollo and Americanist position, but also from a Hispanic one, born from a sense of belonging to an imperial reality and a Catholic intellectual tradition. Triggered by the Enlightenment’s attacks toward Catolicism and Hispanice culture, Clavijero strengthened his identification with the Spanish imperial reality in order to build his defense.